Characteristics associated with uncomplicated pregnancies in women with obesity: a population-based cohort study - Sophie Relph; Yanfang Guo; Alysha L. J. Harvey; Matias C. Vieira; Daniel J. Corsi; Laura M. Gaudet; Dharmintra Pasupathy (BMC, 2021)
Abstract Background Approximately one in five pregnant women have obesity. Obesity is associated with an increased risk of antenatal, intrapartum, and perinatal complications, but many women with obesity have uncomplicated pregnancies. At a time where maternity services are advocating for women to make informed choices, knowledge of the chance of having an uncomplicated (healthy) pregnancy is essential. The objective of this study was to calculate the rate of uncomplicated pregnancy in women with obesity and evaluate factors associated with this outcome. Methods This prospective cohort study was conducted using the Ontario birth registry dataset in Canada (703,115 women, April 2012-March 2017). The rate of uncomplicated or complicated composite pregnancy outcomes (hypertensive disorders of pregnancy, gestational diabetes, preterm birth, neonate small- or large- for gestational age at birth, congenital anomaly, fetal death, antepartum bleeding or preterm prelabour membrane rupture) were calculated for women with and without obesity. Associations between uncomplicated pregnancy and maternal characteristics were explored in a population of women with obesity but without other pre-existing co-morbidities (e.g., essential hypertension) or obstetric risks identified in the first trimester (e.g., multiple pregnancy), using log binomial regression analysis. Results Of the studied Ontario maternity population (body mass index not missing) 17·7% (n = 117,236) were obese. Of these 20·6% had pre-existing co-morbidities or early obstetric complicating factors. Amongst women with obesity but without early complicating factors, 58·2% (n = 54,191) experienced pregnancy without complication; this is in comparison to 72·7% of women of healthy weight and no early complicating factors. Women with obesity and no early pregnancy complicating factors are more likely to have an uncomplicated pregnancy if they are multiparous, younger, more affluent, of White or Black ethnicity, of lower weight, with normal placental-associated plasma protein-A and/or spontaneously conceived pregnancies. Conclusions The study demonstrates that over half of women with obesity but no other pre-existing medical or early obstetric complicating factors, proceed through pregnancy without adverse obstetric complication. Care in lower-risk settings can be considered as their outcomes appear similar to those reported for low-risk nulliparous women. Further research and predictive tools are needed to inform stratification of women with obesity.